Proceedings of the 22nd ACM SIGSOFT International Symposium on Foundations of Software Engineering 2014
DOI: 10.1145/2635868.2635920
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of flaky tests

Abstract: Regression testing is a crucial part of software development. It checks that software changes do not break existing functionality. An important assumption of regression testing is that test outcomes are deterministic: an unmodified test is expected to either always pass or always fail for the same code under test. Unfortunately, in practice, some testsoften called flaky tests-have non-deterministic outcomes. Such tests undermine the regression testing as they make it difficult to rely on test results.We presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
305
6
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 340 publications
(336 citation statements)
references
References 27 publications
20
305
6
5
Order By: Relevance
“…This investigation can be considered as a large-scale replication of the study proposed by Luo et al [18], who performed a similar analysis inspecting 201 commits that likely fix flaky tests. With RQ 2 our goal is to perform a fine-grained investigation into the relationship between test smells and flaky tests.…”
Section: Empirical Study Definition and Designmentioning
confidence: 76%
See 4 more Smart Citations
“…This investigation can be considered as a large-scale replication of the study proposed by Luo et al [18], who performed a similar analysis inspecting 201 commits that likely fix flaky tests. With RQ 2 our goal is to perform a fine-grained investigation into the relationship between test smells and flaky tests.…”
Section: Empirical Study Definition and Designmentioning
confidence: 76%
“…These causes have been classified by relying on the taxonomy proposed by Luo et al [18], who identified ten common causes of test flakiness. Table III reports, for each common cause, a brief description.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations